Visual Cortex Alterations in Early and Late Blind Subjects During Tactile Perception - Ankeeta, A.; Senthil Kumaran, S.; Saxena, Rohit; Dwivedi, Sada N.; Jagannathan, Naranamangalam R. (Perception (London), 2021)
Involvement of visual cortex varies during tactile perception tasks in early blind (EB) and late blind (LB) human subjects. This study explored differences in sensory motor networks associated with tactile task in EB and LB subjects and between children and adolescents. A total of 40 EB subjects, 40 LB subjects, and 30 sighted controls were recruited in two subgroups: children (6–12 years) and adolescents (13–19 years). Data were acquired using a 3T MR scanner. Analyses of blood oxygen level dependent (BOLD), functional connectivity (FC), correlation, and post hoc test for multiple comparisons were carried out. Difference in BOLD activity was observed in EB and LB groups in visual cortex during tactile perception, with increased FC of visual with dorsal attention and sensory motor networks in EB. EB adolescents exhibited increased connectivity with default mode and salience networks when compared with LB. Functional results correlated with duration of training, suggestive of better performance in EB. Alteration in sensory and visual networks in EB and LB correlated with duration of tactile training. Age of onset of blindness has an effect in cross-modal reorganization of visual cortex in EB and multimodal in LB in children and adolescents.